Strains of Akanthomyces uredinophilum, Simplicillium lanosoniveum, and Trichoderma spp. exhibit high endophytic activity and induce improved growth of coffee plants - Martínez-de-Jesús, Juana Margarita (2025)
The cultivation of coffee (Coffea arabica L.) is affected by rust (Hemileia vastatrix), causing losses of over 70% in production. The use of endophytic fungi is a biological strategy for disease control. The objective of this study was to evaluate the endophytic activity of 14 fungal strains and their effect on the growth of coffee plants var. Caturra. Coffee seeds were inoculated with a concentration of 1×106 conidia mL-1 of water, planted and organized in a completely randomized experimental design, with three repetitions of eight plants per strain. At 30, 60, and 120 days after seedling emergence, samples of five leaf segments per plant, 5 mm in diameter, were taken to evaluate endophytic activity. The start of fungal growth (days), initial fungal growth (%) and total fungal growth (%) were recorded. To evaluate the effect of fungal strains on the growth of coffee plants, plant height, stem diameter, number of leaves, leaf pairs, number of branches and chlorophyll content index were evaluated. Analysis of Variance and Tukey's mean separation test (p ≤ 0.05) were performed. Three strains of A. uredinophilum (CHE-CNRCB 435, 616, and 988), two of S. lanosoniveum (CHE-CNRCB 438 and 544), and three of Trichoderma (CHE-CNRCB 398, 1057, and 1062) showed endophytic activity higher than 70%. The three Trichoderma spp. strains induced better growth in coffee plants.